(untitled) (Advances in Oceanography and Limnology, 2013)
Three microbial enzymatic activities involved in organic matter transformation (Leucine AminoPeptidase, LAP, β-glucosidase, β-GLU and Alkaline Phosphatase, AP) and prokaryotic abundance were studied in the Straits of Messina upwelling system. Samplings were performed monthly, between June 2003 and March 2004, at three stations with different hydrodynamic patterns. Potential hydrolysis rates were estimated using specific fluorogenic substrates. Unlike total prokaryotic abundances, quite spatially homogeneous, enzymatic values described different scenarios for each examined station. At the southern Sicilian side (Scaletta) the highest average activity rates were recorded (LAP: 72.19 ± 19.14 nmol Cleu dm−3h−1, β-GLU, 12.53 ± 3.15 nmol Cglu dm−3h−1, AP, 113.59 ± 35.47 nmol PO4dm−3h−1), while at the Calabrian side (Pellaro) the minimum values of LAP, β-GLU and AP were measured. Enzymatic activity values showed seasonal patterns everywhere, with summer values which were one order of magnitude higher than those recorded in other seasons and autumn values which sharply decreased. During winter, the enhanced rates of β-GLU and AP suggested the occurrence of active polysaccharide decomposition and phosphorus regeneration. The variability in the enzymatic activity patterns recorded in the Straits area was indicative of biogeochemical features differing among the examined stations; this resulted in changes in the balance between production and decomposition processes.